Thirty‐Year Trends in the Incidence of Atrial Fibrillation: The ARIC Study - Kunali P. Ghelani; Lin Yee Chen; Faye L. Norby; Elsayed Z. Soliman; Silvia Koton; Alvaro Alonso (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Long‐term data to study recent trends in the incidence of atrial fibrillation (AF), overall and among sex and race groups, are scarce. We evaluated the 30‐year trends in the incidence of AF in the ARIC (Atherosclerosis Risk in Communities) study cohort and explored race and sex differences in these trends. Methods and Results We included 15 343 men and women aged 45 to 64 years in 1987 to 1989 without AF from 4 US communities in the ARIC cohort. Incident AF was identified based on study ECGs, hospital discharge codes, and death certificates through 2017. We calculated age and period‐specific incidence rates (IRs) of AF. We used Poisson regression to calculate IR ratios of AF over time adjusting for age, sex, and race. A total of 3241 AF cases were identified during a mean (SD) follow‐up of 22 years (8.4 years) (599 in Black participants, 2642 in White participants, 1582 in women, and 1659 in men). Overall, the IR of AF in the ARIC cohort was 9.6 per 1000 person‐years (6.9 in Black participants, 10.5 in White participants, 8.1 in women, and 11.6 in men). Age‐specific IR by time period did not show significant changes over time. In a model adjusted for sex, race, and age group, the rate of AF did not change significantly from 1987 to 1991 compared with 2012 to 2017 (IR ratio, 1.10 [95% CI, 0.88–1.36] comparing 2012–2017 with 1987–1991). Similarly, no evidence of changes over time in AF rates were identified in men and women or White and Black participants separately. Conclusions Even though IRs of AF increase as age increases, our analysis provided evidence suggesting that the overall IRs of AF have not changed over time in a multicenter cohort of Black and White individuals in the United States from 1987 to 2017.